Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Appendix D - Graphing Techniques - Exercises - Page 449: 58

Answer

Refer to the curve in Black in Graph I
1506958362

Work Step by Step

For $f(x) = -3(x - 2)^2 + 1,$ when $x = 4, y = -11;$ $x = 3, y = -2;$ $x = 2, y = 1;$ $x = 1, y = -2;$ $x = 0, y = -11$ As seen, $f(x) = -3(x - 2)^2 + 1$ is the horizontal translation to the right by 2 units, the vertical stretching by three times, the reflection across the $x$-axis and the vertical translation up by 1 unit of $f(x) = x^2$. Domain = $(−\infty, \infty)$ Range = $(-\infty, 1]$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.